International Relations of the Middle East - Fawcett, Louise (Oxford, 2005)
In this book, leading scholars of the Middle East and International Relations present a balanced and comprehensive analysis of the international politics of the region. While offering an historical framework, and up-to-date analysis of contemporary events, the book also introduces key theories and concepts from the study of International Relations and applies them to a Middle Eastern context to help explain major currents and developments. The first section offers an historical and chronological overview of the principal developments in the international politics of the Middle East within the broader context of an evolving international system. In this, and later sections, the implications of both September 11, 2001, and intervention in Iraq in the spring of 2003 will be discussed. The second section considers region specific conflicts and issues - the Arab-Israel crisis, wars in the Gulf, US and European policy - and examines them from an international relations perspective. The third and final section looks at major themes in International Relations - globalization, democratization, cooperation and conflict - and applies them to the Middle East, offering a regionally-sensitive perspective.
Keywords: Foreign Relations